Use of Dialectics in Literary Texts (In the Example of the Works of Murad Muhammad Dost) - Khamidov Abdumalik Kironovich (International Journal on Integrated Education, 2022)
In the years of independence, a new period of the linguistic study of literary text began in Uzbek linguistics. After our country was an independent country, the study of national history, literature, and language on a large scale had given special importance. In scientific research, attention have been paid to the study of the language of the literary work, the language and style of the writer, to the analysis of all aspects of the linguistic means in literary texts.